1985
DOI: 10.1128/aac.28.1.58
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of BMY-28142 against pediatric pathogens, including isolates from cystic fibrosis sputum

Abstract: The antibacterial activity of BMY-28142, a new aminothiazole cephalosporin, was measured by standardized broth microdilution and agar dilution methods against 450 gram-positive and gram-negative bacteria isolated from pediatric infections, including acute pulmonary exacerbations of cystic fibrosis. BMY-28142 activity was compared with that of aminoglycosides, 13-lactams, chloramphenicol, trimethoprim-sulfamethoxazole, vancomycin, and clindamycin. The activity of BMY-28142 in combination with other antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…This is in agree ment with reports of other investigators [1,3,11] who have reported high activity of cefepime also against E. cloacae, Serratia marcescens, and M. morganii and against ceftazidime-and cefotaxime-resistant gram-negative bacilli. The compound showed similar activity as that of cefti buten, was twofold or more active than ceftazidime, and was manifold more ac tive than piperacillin/tazobactam against the gram-negative bacilli [7], Strains of Acinetobacter sp.…”
Section: Discussionsupporting
confidence: 82%
“…This is in agree ment with reports of other investigators [1,3,11] who have reported high activity of cefepime also against E. cloacae, Serratia marcescens, and M. morganii and against ceftazidime-and cefotaxime-resistant gram-negative bacilli. The compound showed similar activity as that of cefti buten, was twofold or more active than ceftazidime, and was manifold more ac tive than piperacillin/tazobactam against the gram-negative bacilli [7], Strains of Acinetobacter sp.…”
Section: Discussionsupporting
confidence: 82%
“…Increases in MICs due to higher inoculum densities are well documented among ,-lactam antibiotics (1,4). The fact that a fourfold or lower increase in the MIC was seen when the inoculum density was increased 100-fold for all organisms tested except beta-lactamase-producing H. influenzae is encouraging.…”
mentioning
confidence: 65%
“…1). The compound has excellent activity against a broad spectrum of clinically important pathogens, including Staphylococcus aureus and Pseudomonas aeruginosa strains resistant to other new, broadspectrum cephalosporins (6,9,24).Extensive preclinical safety evaluations have been conducted with cynomolgus monkeys and rats, the latter being appreciably more susceptible to toxicity at high cefepime doses. The present study was conducted to characterize cefepime disposition in these species after single-dose administration.…”
mentioning
confidence: 99%
“…1). The compound has excellent activity against a broad spectrum of clinically important pathogens, including Staphylococcus aureus and Pseudomonas aeruginosa strains resistant to other new, broadspectrum cephalosporins (6,9,24).…”
mentioning
confidence: 99%